Peran Perayaan Isra Mi’raj melalui Kompetisi Salat terhadap Nilai Spiritual Anak Jorong Lembang Bukik Sileh - Dea Ananda Insyira; Gustina Erlianti; Lulu Hikmah Saputri; Neisha Mella Nur Chaila; Amon Zamora (CV. ITTC INDONESIA, 2026)
The Isra Miraj celebration is an important occasion for instilling religious and spiritual values in children. This community service activity was conducted in Jorong Lembang Bukik Sileh with the aim of enhancing children's spiritual values through a prayer competition. The activities included competitions in fardu ain and fardu kifayah prayers, designed to improve children's understanding, skills, and awareness in performing worship according to Islamic teachings. The methods employed consisted of socialization, training, mentoring, and the implementation of the competition involving local children. The results indicated an improvement in children's understanding of prayer procedures, worship discipline, self-confidence, and enthusiasm for participating in religious activities. Furthermore, the program strengthened religious character development and social awareness within the community. Therefore, the Isra Miraj celebration through prayer competitions serves as an effective means of enhancing the spiritual values of children in Jorong Lembang Bukik Sileh.